2019
DOI: 10.1101/809319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HypermutatorPseudomonas aeruginosaexploits multiple genetic pathways to develop multidrug resistance during long-term infections in the airways of cystic fibrosis patients

Abstract: 21 cystic fibrosis 22 WORD COUNT ABSTRACT: Abstract, 249 words. Importance, 147 words 23 WORD COUNT TEXT: 4995 words.24 2 25 ABSTRACT 26 Pseudomonas aeruginosa exploits intrinsic and acquired resistance mechanisms to resist almost 27 every antibiotic used in chemotherapy. Antimicrobial resistance in P. aeruginosa isolated from 28 cystic fibrosis (CF) patients is further enhanced by the occurrence of hypermutator strains, a 29 hallmark of chronic CF infections. However, the within-patient genetic diversity of P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…Chromosomal inversions were also shown to disrupt the reading frame of mutS and induce hypermutability in clinical strains from the C lineage [39]. Hypermutable isolates, thus, accumulate a mean of 16-fold more mutations, with a median of 48 SNPs per year (range of 2 to more than 350 SNPs per year) [7,8,15,17,45].…”
Section: Hypermutabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal inversions were also shown to disrupt the reading frame of mutS and induce hypermutability in clinical strains from the C lineage [39]. Hypermutable isolates, thus, accumulate a mean of 16-fold more mutations, with a median of 48 SNPs per year (range of 2 to more than 350 SNPs per year) [7,8,15,17,45].…”
Section: Hypermutabilitymentioning
confidence: 99%
“…Indeed, it has been shown that antibiotic exposure promotes the emergence of hypermutability in P. aeruginosa, then favouring acquisition of antibiotic resistance [45,[48][49][50][51]. However, Mehta and colleagues also observed that some hypermutable lineages would spontaneously decline and disappear from the evolving population [49].…”
Section: Hypermutabilitymentioning
confidence: 99%
“…Since mutation rates must be precisely controlled to avoid extensive accumulation of deleterious mutations and to prevent genomic instability, the overexpression of mutator alleles should be driven from tightly-regulated expression systems (which is always challenging, irrespective of the bacterial host 74 ) or during short periods of time. Thus, the easy-to-cure mutator plasmids developed in this study, which can be rapidly removed from isolated clones displaying the phenotype of interest, offer a clear advantage over conventional mutator strains—where the mutator phenotype is elicited by genomic (hence, essentially irreversible) modifications, as epitomized by the emergence of mutator phenotypes of P. aeruginosa in clinically-relevant setups 75-77 . In contrast with the results of the ChnR/P chnB -dependent module, the thermoinducible mutator devices allowed for a tightly- regulated expression of mutL E36K .…”
Section: Resultsmentioning
confidence: 99%
“…Although the accumulation of beneficial traits along with many neutral or deleterious ones may be the consequence of a higher mutation rate, the mutator phenotype itself is unseen by selection. Rather, mutators evolve by the indirect effects of selection on linked traits, such as loss of acute virulence in CF, increased biofilm formation, metabolic adaptations, and antibiotic resistance ( 51, 53, 58, 8385 ). The probability of this linkage increases in small populations under strong selection that are limited for beneficial genetic variation or under conditions when effects of drift relative to selection are amplified ( 86 ).…”
Section: Discussionmentioning
confidence: 99%